Byproduct fuel stove - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
A stove adapted by the International Rice Research Institute (IRRI) from a Vietnamese design not only cooks rice more quickly, it is also environmentally-friendly and uses virtually free fuel. The stove called the Ipa-Qalan, uses rice hull waste...